Nerve growth factor (NGF) differentially regulates the chemosensitivity of adult rat cultured sensory neurons - Bevan, S (J Neurosci, 1995)
We have studied the effects of NGF on the chemosensitivity of adult rat DRG neurons over a 1–2 week period in vitro, using voltage-clamp and radioactive ion flux methods. A sustained proton evoked current was reversibly lost in NGF-free medium after 1 week. Proton-evoked efflux of radioactive 86Rb+ ions was also depressed in NGF deprived cultures, although depolarization with 40 mM potassium still evoked a large 86Rb+ efflux. A similar reversible loss of capsaicin sensitivity was noted. The response to GABA and a second, transient proton evoked current were also regulated by NGF, but over a longer time course. In contrast, the sensitivity to ATP was not influenced by the presence or absence of NGF. These data show that NGF regulates some, but not all, chemosensitivities of DRG neurons and that loss of sensitivity occurs at different rates for different agonists. The precise co-regulation of the response to capsaicin and the sustained response to protons provides further evidence that protons activate capsaicin-operated ion channels.